Impact of COVID-19 Pandemic on Infertility-Related Stress in Women Undergoing Intrauterine Insemination Cycle - Azad, Nahid; Azargoon , Azam; Yousefi, Behpour; Hemmatian, Najme; Ziari, Abbas; Naderi Eram , Maryam (Novelty in Biomedicine, 2023)
Background: Infertility remains an important problem with a significant negative social impact on infertile couples. intrauterine insemination (IUI) is an assisted method of infertility treatment in couples with unexplained and mild/moderate male factor subfertility. In the present study, we compared infertility-related stress in women undergoing the IUI cycle before and after COVID-19 Pandemic. Materials and Methods: One hundred and sixty women undergoing the IUI cycle participated in the present study. Samples were collected from Jun 2019 to December 2019 and postponed for 6 months because of COVID-19 Pandemic. Afterward, sampling was started again in March 2021. The sampling was divided into two parts, including (I) before and (II) after COVID-19 Pandemic. A socio-demographic form and Fertility Problem Inventory (FPI) questionnaire were completed by participants before starting their treatment. Statistical analyses were performed using Prism software. Results: According to the results of FPI questionnaires, ~95% of all women participating in the study showed medium to very high levels of total infertility stress. The mean total scores of FPI in patients before and after the COVID-19 Pandemic groups were 137.6 ± 24.8 and 134.6 ± 27, respectively. The comparison of FPI scores between the two groups exhibited no significant difference (P˃0.05). Findings also showed that total infertility stress was significantly associated with age, duration of infertility, employment, and educational status. No significant relationship was found between total infertility stress and other data (cause of infertility, type of infertility, and history of previous IUI). Conclusion: According to our study, COVID-19 Pandemic did not affect infertility-related stress in infertile women.